2021
DOI: 10.1007/s10943-021-01285-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 and Religious Restrictions on the Well-Being of Ghanaian Christians: The Perspectives of Religious Leaders

Abstract: In response to the COVID-19 pandemic, the Ghana government instituted a ban on social gatherings, including religious gatherings. To understand how the unanticipated restrictions and interruption in normal church routines affected the well-being of congregants in Ghana, we interviewed 14 religious leaders. Thematic analysis revealed psychospiritual impacts including decline in spiritual life, loss of fellowship and community, financial difficulties, challenges with childcare, as well as fear of infection. Reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…In particular, the content of health communications may aim to emphasize perceived efficacy especially in contexts where efficacy beliefs are weaker, but communicators may also consider the perceived degree of threat posed by the disease. In addition, the source of health communication should be appropriate to the cultural context (for an example highlighting the role of religious leaders see: Osei-Tutu et al, 2021a ). In Italy, the initial high confidence in the national healthcare system may have led to underestimation of the risks of the pandemic, and this suggests that in the face of diseases with unknown seriousness and harmfulness, it is important to adopt a prudent attitude by emphasizing the potential dangers rather than downplaying them.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the content of health communications may aim to emphasize perceived efficacy especially in contexts where efficacy beliefs are weaker, but communicators may also consider the perceived degree of threat posed by the disease. In addition, the source of health communication should be appropriate to the cultural context (for an example highlighting the role of religious leaders see: Osei-Tutu et al, 2021a ). In Italy, the initial high confidence in the national healthcare system may have led to underestimation of the risks of the pandemic, and this suggests that in the face of diseases with unknown seriousness and harmfulness, it is important to adopt a prudent attitude by emphasizing the potential dangers rather than downplaying them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most women considered not following health protocols as harming their own health and the health of others, so they tried to follow these protocols as much as possible. In general, various studies have shown that during the COVID-19 pandemic, the number of religious practices increased and most people prayed or performed religious acts to end COVID-19 (42). Yoosefi lebni et al 2021 in a study conducted among housewives in Iran during the COVID-19 period reported that women resorted to religious practices such as praying, supplication, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, more attention has been given to the impact of Covid-19 upon socio-economic variables like mental and reproductive health, education, disability, and gender-based violence than religious practice. Nonetheless, there is some scholarly literature on the impact of the pandemic on religiosities from South Africa, Zimbabwe, Nigeria, Ghana, and Kenya (Sibanda, Muyambo, & Chitando 2022;Udok, Eton, & Akpanika 2020;Osei-Tutu, Affram, Mensah-Sarbah, Dzokoto, & Adams 2021;Omopo 2021;Chukwuma 2021;Sambu, Kweingoti, Cherotich, & Salimin 2021:9 of 18). An internet search for any scholarly work on the impact of the pandemic on religious practices in Uganda was futile, with the exception of studies in which religion was used as a variable of analysis of the people's understanding of Covid-19 (Isiko 2020a;Echoru et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%